Range of motion study of the hip and knee in prayer by Muslims: a preliminary report - Arshad, Ahmad Afiq; Johari, Muhammad Hafiz; Rahimin, Muhammad Ali Sajjad; Sharifudin, Mohd Ariff (International Islamic University Malaysia, 2014)
Background and Objectives: Praying or solah, represent a paramount and fundamental activity of daily living in Muslim community. Muslims need to adopt several postures that require deep flexion of the knee and hip to perform this daily obligation. The increased in demand of joint flexion has been the focus of research into development of knee and hip replacement implants suitable for Asian Muslim population. However, there is a lack of data on normative range of motion studies pertaining to these joints in relation to the postures in prayer by the Muslims. The aim of this study is to simultaneously obtain normative passive and functional range of flexion data during prayer by Muslims in the knee and hip joints of normal adults.